2020
DOI: 10.3390/s20164396
|View full text |Cite
|
Sign up to set email alerts
|

Glacier Surface Motion Estimation from SAR Intensity Images Based on Subpixel Gradient Correlation

Abstract: With the current extensive availability of synthetic-aperture radar (SAR) datasets with high temporal (e.g., a repeat cycle of a few or a dozen days) and spatial resolution (e.g., in the order of ∼1 m), radar remote sensing possesses an increasing potential for the monitoring of glacier surface motion thanks to the nearly weather and time-independent advantages. This paper proposes a robust subpixel frequency-based image correlation method for dense matching and integrates the improved matching into a workflow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 67 publications
0
3
0
2
Order By: Relevance
“…The frequency correlator of COSI-Corr estimates the phase difference in the Fourier domain and uses a bell-shaped function to avoid edge effects, and is less sensitive to outliers [31]. Fang et al [32] suggested that phase correlation in COSI-Corr with larger matching windows can achieve the best and most robust glacier motion estimation when applied to optical Landsat images. For fast-moving ice, Landsat image pairs with short repeat cycles (between 32 and 80 days) and ERS-1/2 image pairs with a 35-day repeat cycle are preferred.…”
Section: Ice Flow Velocity Extractionmentioning
confidence: 99%
“…The frequency correlator of COSI-Corr estimates the phase difference in the Fourier domain and uses a bell-shaped function to avoid edge effects, and is less sensitive to outliers [31]. Fang et al [32] suggested that phase correlation in COSI-Corr with larger matching windows can achieve the best and most robust glacier motion estimation when applied to optical Landsat images. For fast-moving ice, Landsat image pairs with short repeat cycles (between 32 and 80 days) and ERS-1/2 image pairs with a 35-day repeat cycle are preferred.…”
Section: Ice Flow Velocity Extractionmentioning
confidence: 99%
“…In recent decades, the optical image correlation technique for measuring displacement of features in earth and geological science has been widely used. In the feature tracking method, two images are correlated to measure displacement and one image is treated as a master image whereas the other is a slave [11,35]. In this technique, a matrix is selected on the master image with some center and the same window is dug out from the slave image and both are compared using similar function.…”
Section: Introductionmentioning
confidence: 99%
“…Wherefore, the offset-tracking method is mainly used in ice-covered areas, where velocities are significant and major displacements appear in the horizontal plane. This technique is widely used to obtain glacier surface velocities (yan et al 2013, Strozzi et al 2017, Fang et al 2020, Neckel et al 2020 but also displacement values in mining areas (Huang et al 2016, 2020, Zhao et al 2021 or even in the areas of landslides (Cai et al 2017;Sun et al 2017) or sand dunes (Mahmoud et al 2020). The accuracy of this method is determined as 1/10-1/30 of the pixel size (Fan et al 2019).…”
Section: Introductionmentioning
confidence: 99%